2015
DOI: 10.1038/nrmicro3546
|View full text |Cite
|
Sign up to set email alerts
|

c-di-GMP signalling and the regulation of developmental transitions in streptomycetes

Abstract: The complex life cycle of streptomycetes involves two distinct filamentous cell forms: the growing (or vegetative) hyphae and the reproductive (or aerial) hyphae, which differentiate into long chains of spores. Until recently, little was known about the signalling pathways that regulate the developmental transitions leading to sporulation. In this Review, we discuss important new insights into these pathways that have led to the emergence of a coherent regulatory network, focusing on the erection of aerial hyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
198
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 159 publications
(204 citation statements)
references
References 105 publications
3
198
1
2
Order By: Relevance
“…BldD is located at the top of the regulatory hierarchy that controls morphological differentiation in Streptomyces species, serving as the transcriptional repressor of sporulation genes (8). In this study, we showed that the BldD orthologue AmBldD plays an important role in the morphological differentiation of A. missouriensis.…”
Section: Discussionmentioning
confidence: 64%
“…BldD is located at the top of the regulatory hierarchy that controls morphological differentiation in Streptomyces species, serving as the transcriptional repressor of sporulation genes (8). In this study, we showed that the BldD orthologue AmBldD plays an important role in the morphological differentiation of A. missouriensis.…”
Section: Discussionmentioning
confidence: 64%
“…Whether additional electron shuttle-producing microbes, or those that exploit the shuttles produced by others, have the capacity to control social behavior during this process is not known. However, as electron shuttle production and utilization is observed in phylogenetically disparate organisms (3,12), and developmental regulation by the secondary messenger c-di-GMP is a common bacterial trait (20,47), similar mechanisms could be operating in multicellular communities formed by diverse microbes.…”
Section: Colony Matrix Distribution Phenotypes Suggest That Phenazinementioning
confidence: 99%
“…Streptomycetes are filamentous, antibiotic-producing soil bacteria that have a multicellular life cycle with two distinct modes of cell division: vegetative cross-wall formation and sporulation septation (11) (Fig. 1A).…”
mentioning
confidence: 99%